The Correlation Impact Between Problem-Based Learning and Students Interest When Learning English In Junior High School - Risna; Ida Wardani; Yuni Utami Asih (Universitas Islam Negeri Palopo, 2025)
This study investigates the correlation between the implementation of Problem-Based Learning (PBL) and students' interest in learning English at the junior high school level. PBL is a student-centered pedagogical approach that engages learners in solving real-world problems to develop critical thinking, collaboration, and communication skills. The primary research question examines whether the application of PBL significantly influences students’ interest in English language learning. Employing a quantitative correlational design, the study involved 50 eighth-grade students from a public junior high school in Indonesia. Data were collected through structured questionnaires assessing perceptions of PBL and levels of interest in English learning. The results, analyzed using the Pearson Product-Moment correlation test, revealed a significant positive relationship (r = 0.630, p = 0.000), indicating that increased implementation of PBL correlates with higher student interest. These findings underscore the potential of PBL to enhance student engagement and motivation. English language educators are encouraged to adopt PBL strategies to foster more meaningful and interactive learning environments.